Field and greenhouse screening for resistance to leafhoppers and thrips in cowpea - Raman, K.V. (International Institute of Tropical Agriculture, 1976)
Of 4705 entries in the World Cowpea Germplasm Collection, 800 showed moderate to high levels of field resistance to Sericothrips occipitalis and Empoasca dolichi and of these 100 were highly resistant. Of six lines tested under greenhouse conditions, TVu662E was highly resistant to E. dolichi, resistance being the result of antibiosis.